Initial crown diameter influences on the fruit yield and quality of strawberry pircinque - Fagherazzi A.F.* (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland.In strawberry production, the combination of a high productive performance and fruits with desirable physicochemical characteristics requires the use of plants with a good quality and high initial vigor. This study aimed to evaluate the effect of plants with different crown diameters on the productive performance and fruit quality of strawberry plants of the cultivar ‘Pircinque’ (Short Day). The study was conducted in two evaluation cycles (2016/2017 and 2017/2018). The experimental design was divided into randomized blocks, with four repetitions, and plots consisting of 20 plants. This study evaluated the crown diameters of plants of 5, 7, 9, 11, 13, 15, 17, and 19 mm. The productivity and number of fruit values increased significantly by 57% with larger caliber plants, which also provided precocity of productivity. The use of more vigorous plants also favored the production of fruits with higher soluble solids/titratable acidity ratios (+28%) and with epidermis coloration closer to intense red (−4.3%). For the cultivar ‘Pircinque’, plant crown diameters between 15 and 17 mm are the most favorable because they condition the best productive performances in combination with precocity and a good fruit quality.